'Listen to the atmosphere!': On spectator sounds and their potentially disruptive role in a football simulation video game. Issue 1 (1st August 2020) - Graakjær, Nicolai Jørgensgaard
This article aims to specify the role of spectator sounds in football simulation video games as exemplified by FIFA 19: what are the structures and functions of spectator sounds and how are these sounds related to the visuals of the video game and the player's actions and potential experience of disruption? Although the examination generally adds to the understanding of a prevalent and purportedly significant yet hitherto rather underexplored type of video game sound, the examination also motivates a modification of certain positions within previous research that has routinely highlighted the non-obtrusive role of video game sounds. Specifically, the article shows how the disruptive potential of the spectator sounds is attributional both to what they sound like, why they occur and how and from what perspective the player is called upon to listen to them.